2010
DOI: 10.1016/j.otohns.2010.06.908
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency inferior turbinate reduction: An evaluation of olfactory and respiratory function

Abstract: RITR may provide excellent outcomes in terms of improvement in olfactory function and nasal flow in patients affected by turbinate hypertrophy refractory to medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
(48 reference statements)
0
35
0
Order By: Relevance
“…During the 3 rd and 6 th month follow up, no patient was found to have crusting in RFVTR group. Garzaro et al [20] observed mild edema and crusting after 1 week in patients who underwent RFVTR and all the nasal crusting had settled by 3 months. No crusting following RFVTR was reported by many studies.…”
Section: Post-operative Complicationsmentioning
confidence: 97%
See 3 more Smart Citations
“…During the 3 rd and 6 th month follow up, no patient was found to have crusting in RFVTR group. Garzaro et al [20] observed mild edema and crusting after 1 week in patients who underwent RFVTR and all the nasal crusting had settled by 3 months. No crusting following RFVTR was reported by many studies.…”
Section: Post-operative Complicationsmentioning
confidence: 97%
“…[9,14,18,20] SST and ciliary beat frequency are preserved after RFVTR. [18] STT was significantly prolonged at 1 week post-operatively in our series.…”
Section: Saccharin Transit Timementioning
confidence: 97%
See 2 more Smart Citations
“…Recently, Garzaro and colleagues 15 studied smell ability of 40 patients with nasal obstruction caused by ITH before and after RFITR. Anosmia, hyposmia, and normosmia were observed in 2, 33, and 5 patients, respectively, before surgery in contrast with 1, 5, and 34 patients, respectively, after surgery.…”
mentioning
confidence: 99%